2021
DOI: 10.1002/ange.202014348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mapping of Glutathione within Intracranial Tumors through Interlocked MRI Signals of a Responsive Nanoprobe

Abstract: Studies reveal that malignant tumors feature uneven distributions of some key biomarkers across the entire tumorous region. Nevertheless,o nly very limited progress has been made towards non-invasive and quantitative detection of tumor-specific biomarkers in vivo,e specially with clinically compatible imaging modalities.R eported here is an Fe 3 O 4 nanoparticle-based glutathione (GSH) responsive magnetic resonance imaging (MRI) probe that can form particle aggregates within tumors in vivo to give rise to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In addition, the design of TME-responsive MRI contrast agents has been regarded as the research hotpot in recent years, which could significantly increase the imaging sensitivity and enhance the signal-to-background ratio. For example, Zhang et al [111] developed a glutathione (GSH)-responsive MRI probe based on Fe 3 O 4 NPs, which could induce aggregation when encountering the high GSH concentrations in the TME (Fig. 4a).…”
Section: Iron Oxide Npsmentioning
confidence: 99%
“…In addition, the design of TME-responsive MRI contrast agents has been regarded as the research hotpot in recent years, which could significantly increase the imaging sensitivity and enhance the signal-to-background ratio. For example, Zhang et al [111] developed a glutathione (GSH)-responsive MRI probe based on Fe 3 O 4 NPs, which could induce aggregation when encountering the high GSH concentrations in the TME (Fig. 4a).…”
Section: Iron Oxide Npsmentioning
confidence: 99%
“…In neutral pH environment, the assembled particles presented enhanced T 2 ‐weighted signals, while they fell apart in acidic tumor microenvironment to give rise to strong T 1 ‐weighted MR signal. Recently, Gao group constructed a GSH‐responsive MRI probe that can be switched from T 1 to T 2 enhancement due to the GSH‐induced aggregation of the USPIO particles within tumors, which was further demonstrated possible for quantitatively mapping the endogenous GSH in intracranial tumors through MRI (Zhang et al, 2021). In detail, USPIO particles of 3.9 nm simultaneously bearing surface maleimide groups and functional peptide sequences were designed to obtain the probe that displayed a strong T 1 contrast enhancement effect in the absence of GSH.…”
Section: Advantages Of Uspio Nanoparticlesmentioning
confidence: 99%
“…However, it exhibited dramatically enhanced T 2 enhancement in GSH‐rich environment as GSH can reduce the disulfide bonds embedded in the peptide sequence to generate thiol groups that react with the maleimide groups from the adjacent USPIO particles to glue them together. It was further demonstrated that such GSH‐induced particle aggregation could give rise to interlocked T 1 and T 2 signal variations, which were proven to quantitatively correlate with GSH concentration to enable the GSH mapping of intracranial tumor in vivo (Zhang et al, 2021).…”
Section: Advantages Of Uspio Nanoparticlesmentioning
confidence: 99%
“…Nanomaterial-assisted postoperative immunotherapy possesses a greater advantage for preventing long-term recurrence in tumors growing in special locations where resecting additional tissue is highly undesirable, such as brain tumors that possess poor prognosis and high recurrence rates owing to residual cancer cells in the brain. 192 Jiang and coworkers presented an injectable self-fabricating oligopeptide hydrogel system that promotes the tumor-specific immune response after glioblastoma surgical resection, which effectively prevents the recurrence of the brain tumors in mice. The hydrogel serves as the drug reservoir for the co-delivery of CXC chemokine ligand 10 (CXCL10) and tumor-homing immune nanoregulator (THINR).…”
Section: Postoperative Immunotherapy For Recurrence Inhibitionmentioning
confidence: 99%